Alantolactone inhibits oesophageal adenocarcinoma cells through nuclear factor erythroid 2‐related factor 2‐mediated reactive oxygen species increment. Issue 3 (21st December 2022) - Chen, Jianhua; Zhang, Yunxiang; Huang, Rong; Cao, Lihua; Zhang, Ying; Lian, Maowei; Wang, Zuo; Jin, Jiajia; Tang, Chu; Chen, Tingting; Yan, Linli; Yu, Linze; et al.
Abstract: Background: Oesophageal adenocarcinoma (EAC) is a highly lethal cancer associated with a rapidly rising incidence and a poor prognosis. Alantolactone, a sesquiterpene lactone isolated from inula helenium, has anti‐inflammatory, antimicrobial, neuroprotective activities, and anticancer properties. Objective: In the present study, the anticancer effects of alantolactone on the human EAC cells were investigated in vitro and in vivo. Methods and findings: After treated with alantolactone, the cell viability of KYAE‐1, KYAE‐2, OE19, and OE33 cells reduced significantly compared with that of the control cells. Alantolactone induced apoptosis of the EAC cell lines by inhibiting the protein expression levels of nuclear factor erythroid2‐related factor 2 (Nrf2). Furthermore, the apoptosis‐inducing effect of alantolactone was enhanced by Nrf2 knockdown while reduced by overexpression of Nrf2. Antioxidant α‐tocopherol and glutathione can protect EAC cell lines against alantolactone. A xenograft nude mice model showed that alantolactone can inhibit EAC growth in vivo. Conclusions: Alantolactone inhibits oesophageal adenocarcinoma cells through Nrf2‐mediated reactive oxygen species (ROS) increment. Alantolactone maybe a potential therapeutical candidate for treating EAC.